KYNETICS AND THERMODYNAMIC RESEARCH OF LEAD (II) ADSORPTION IN SUGARCANE BAGASSE ASH - Prieto García, Julio Omar; Aguilera Casabella, Diana María; Curbelo Sánchez, Alfredo; Broche Galindo, María H.; Mollineda Trujillo, Ángel (Centro Azúcar Journal, 2019)
Lead adsorption in sugar cane bagasse ash is exposed in present study. The described kinetic models respond to pseudo second and pseudo first order behavior, Elovich and intraparticle diffusion. The analyzed isotherms correspond to the Langmuir, Freundlich, Tóth and Dubinin models. From the kinetic point of view the analyzed cases for temperatures of 25, 40 and 60 C, are adjusted to the pseudo-second order model with an increase tendency for the specific adsorption speed constant when the temperature increases. The isothermal adsorption models respond to Langmuir model for studied temperatures. The isosteric heat value of 0.91 kJ / mole is established and the process activation energy is 10.01 kJ / mole, denoting a physical process of adsorption. The enthalpy variation value is -3.14 kJ / mole and the entropy variation is 0.01 kJ / mole K denoting its low heat evolution and its little relevant system disorder.